Evaluation of the Limited and Gradual Face-to-Face Learning Activity Post the COVID-19 Pandemic at the Faculty of Social Sciences and Law, State University of Surabaya - Prabawati, Indah; Pradana, Galih; Febriyanti, Eni; Haryonno, Hafids (JPSI (Journal of Public Sector Innovations), 2022)
This study aimed to evaluate the limited and gradual face-to-face learning activities at the Faculty of Social Sciences and Law, the Surabaya State University (Unesa), after the Covid-19 pandemic. The Covid-19 pandemic has impacted all sectors of life, including the education sector. After implementing learning using distance methods online for several months, the Faculty of Social Sciences and Law, Unesa, held limited and gradual face-to-face learning activities during the post-pandemic transition period. This study is intended to evaluate these activities. The research method used is descriptive. The analytical framework uses policy evaluation using evaluation criteria which include 1) Effectiveness; 2) Efficiency; 3) Adequacy; 4) Equity; 5) Responsiveness; 6) Appropriateness. The results of this study show that most students consider the implementation of limited and gradual face-to-face learning to be good enough and able to create a conducive learning atmosphere and increase student enthusiasm for learning. However, several things, primarily related to the limited and gradual availability of facilities and infrastructure to support face-to-face lecture activities, need to be considered. Several supporting facilities and infrastructure that need to be added include a portable microphone or Bluetooth headset to support hybrid learning, spare masks, and hand washing soap refills at the sink. One of the limitations of the research is the subjectivity of the researcher. This study relies heavily on the researcher's interpretation of the meaning implied in the interviews; therefore, the possibility of bias remains.